2004
DOI: 10.1055/s-2004-817981
|View full text |Cite
|
Sign up to set email alerts
|

CABG and Bone Marrow Stem Cell Transplantation after Myocardial Infarction

Abstract: We encountered two cases of ruptured anastomotic pseudoaneurysms 47 and 77 months after surgery for atherosclerotic thoracic aortic aneurysms. Autopsy was performed in one case and emergency re-operation was performed in the other case. We gained some interesting findings in the autopsy and the re-operation. The anastomotic sites were sustained by sutures only, and there was no evidence of tissue supplementation at the anastomotic sites in macroscopic observation. Microscopic findings demonstrated endothelium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 14 publications
1
84
0
3
Order By: Relevance
“…Thus these findings support the notion that BMCs adopt the cardiac phenotype and potentiate the growth reserve of the adult heart. Collectively, these observations point to the therapeutic import of BMCs for cardiac diseases in humans (17,39,69,158,163,239,273,372,373,415,421,448,449,452,528).…”
Section: B Hematopoietic Stem Cellsmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus these findings support the notion that BMCs adopt the cardiac phenotype and potentiate the growth reserve of the adult heart. Collectively, these observations point to the therapeutic import of BMCs for cardiac diseases in humans (17,39,69,158,163,239,273,372,373,415,421,448,449,452,528).…”
Section: B Hematopoietic Stem Cellsmentioning
confidence: 89%
“…In spite of these uncertainties, clinical trials have been completed and some are ongoing (39,69,158,163,186,273,372,373,415,421,448,449,452,528). The safety of this approach has been documented, and double-blind clinical studies are in progress.…”
Section: B Hematopoietic Stem Cellsmentioning
confidence: 99%
“…There are no specific studies in the literature on therapeutic revascularization with cell therapy for diabetic patients, although many studies have demonstrated that diabetic patients displayed poorer responses to cell therapy than non-diabetic patients. [20][21][22][23][24][25][26][27][28][29][30] Indeed, Tamarat et al demonstrated a reduced angiogenic potential of EPCs in diabetic animals. Administration of diabetic progenitors into the ischemic hindlimbs of non-diabetic mice improved angiogenic response to a lesser extent.…”
Section: Discussionmentioning
confidence: 99%
“…While there were no significant differences between the groups, patients treated with selected CD34+/CXCR4+ cells showed trends of improvement in LV function when compared to controls. Other studies utilizing primitive populations of BM-SPCs such as CD133+ cells have reported improvement of LV function and perfusion (Bartunek et al, 2005;Stamm et al, 2004).…”
Section: Bm-derived Stem Cell Transplantation For Myocardial Repairmentioning
confidence: 96%